The pedagogist in the hospital toy library : playing as a process of humanizing pre-school children (Revista Brasileira de Iniciação Científica, 2023)
This text aims to reflect on the performance of the pedagogue in hospital toy libraries with the intention of developing the psyche of hospitalized children. Many children remain hospitalized for a long period and are away from school activities, this investigation is justified by the importance of providing opportunities for the psychological development of hospitalized children. To this end, the number of hospital toy libraries in the northwest region of the state of Paraná is expressed and, in the light of the Historical-Cultural theory, aspects of the role of the pedagogue in toy libraries are discussed. It is concluded that the planned action of the pedagogue in the hospital toy library is fundamental in the continuity of the hospitalized child's development.
Keywords: Organization of teaching.; Development of the psyche.; Child education.; Role games.